Comparison of the liquid and lyophilized formulations of Prolastin®-C for Alpha1-Antitrypsin deficiency: Biochemical characteristics, pharmacokinetics, safety and neoantigenicity in rabbits. (November 2019) - Arora, Vikram; Cruz, Maria; Lang, John; Klos, Anthony M.; Merritt, W. Keither; Price, Jeffrey; Taylor, George; Vandeberg, Pete; Wee, Kevin; Willis, Todd
Abstract: Multiple analytical and preclinical studies were performed to compare the biochemical characteristics, pharmacokinetics (PK), safety and neoantigenicity of a new 5% liquid formulation of Alpha-1 Proteinase Inhibitor (Liquid A1PI, Prolastin®-C Liquid) with the lyophilized version (Lyophilized A1PI, Prolastin®-C). Liquid A1PI and Lyophilized A1PI had similar average mass ( 52 kDa), and both forms exhibited glycoform patterns consistent with the known banding pattern of A1PI (dominated by the M6 and M4 bands, including deconvoluted masses). Both Liquid A1PI and Lyophilized A1PI yielded average percent purity values ranging from 96% to 99% and had active content ranging from 53 mg/mL to 59 mg/mL. The PK profile of Liquid A1PI was similar to Lyophilized A1PI. Safety assessments in rabbits showed good tolerability and no test article-related changes in mortality, clinical signs, clinical pathology, body weight, food consumption, or urinalysis parameters. Following immunodepletion of antibodies that recognize Lyophilized A1PI, there were no significant differences in the anti-drug titers among animals immunized with Lyophilized A1PI and Liquid A1PI ( p > 0.05), indicating that no antibodies to neoantigens were generated. Liquid A1PI and Lyophilized A1PI have similar profiles with respect to biochemical characteristics, PK, safety and neoantigenicity.